L’intoxication Par Les Cremes Eclaircissantes Au Maroc Profil Epidemiologique - Bellaje Rajaa; Houda Sefiani; Doha Benali; Soulaymani abdelmajid; Soulaymani Bencheikh Rachida (European Scientific Journal, ESJ, 2016)
Objectives: In Morocco the large number of cosmetic products is sold freely without control or registration. The lack of knowledge of the composition of these products make therapeutic management in case of poisoning very difficult and sometimes causes unnecessary health spending even if these poisoning are often benign. The objective of this study is to establish the epidemiological profile of a poisoning by lightening creams collected at the Moroccan Poison Control and Pharmacovigilance Center. Methods: This is a retrospective study of poisoning case by lightening creams collected at the Moroccan Poison Control and Pharmacovigilance Center between 1992 and 2008. Results: During the study period, 95 cases were collected. The mean age is 20 years ± 1.4 [1-70 ans], and the F/M sex ratio is 1.73. In 90 (95%) cases, the route of poisoning was oral. The Suicide attempts represent 33 % of cases. Women are often voluntarily intoxicated. However, men were concerned by involuntary intoxication (p = 0.003). Eighty three cases were urban (87%) and 90 cases occured at home (95%). The digestive disorders were found in 68 cases associeted or not with a neurological disorders (33 cases), cardiovascular disorders (14 cases), and respiratory distress (6 cases). The evolution was favorable in all cases. Conclusions: The implementation of the new law recording to the registration of cosmetic products in the ministry of health before marketing will ensure certainly a better orientation of the poisoning case management and improve the patient safety.